Water quality hazard assessment for hand dug wells in Rafin Zurfi, Bauchi State, Nigeria - Jagaba, A.H. (Ain Shams University, 2020)
The Nigeria Centre for Disease Control recently reported an outbreak of yellow fever in Bauchi state. To strategize mitigation measures, an investigation into water sources became necessary. This study adopted Water Quality Index (WQI), Target Hazard Quotient (THQ) and Hazard Index (HI) approaches to evaluate water quality from hand-dug wells within Rafin Zurfi area, Bauchi State. The specific objectives were; sample characterization, statistical analysis by SPSS, and determination of health risk analysis by WQI. Water from Hand-dug wells were examined using standard methods of the American Public Health Association (APHA). Experimental results proved that pH values of samples are adequate according to NSDWQ, while samples E and L exceeded the WHO permissible limits. Turbidity, Total hardness, TSS, EC, BOD, Ca, SO42â, Clâ, Cu and Zn measurements were all within permissible limits. The analytical results were taken in to Geographic Information Systems environment (GIS) to generate numerical spatial variation maps for parameters examined and show the health risk associated to heavy metals. HI values for adults and children were found to be 4.365119 Ã 10â3 and 5.180528 Ã 10â3, respectively. Therefore, the study concludes that, there is no significant danger of metal toxicity from the sample wells (since HI < 1). Â© 2020 Faculty of Engineering, Ain Shams University